PERANCANGAN PENGOLAHAN AIR MINUM TENAGA SURYA KAPASITAS 50 M3/HARI (Dengan Menggunakan Proses Biofiltrasi Dan Ultrafiltrasi) - Setiaji, Galih; said, nusa idaman (Center for Environmental Technology, 2016)
Drinking water supply for public is big deals for the improvement of environmental and society health. An effort from the government to provide the drinking water supply is to provide a society based of drinking water treatment plant. Some obstacles that have come for the plant in remote areas are the difficulties of getting chemical material for the plant and the lack of energy supply. Drinking water treatment that use chemical materials has a big cost to provide the chemicals. Beside the high cost of treatment, the using of chemicals will harmful the drinking water, because it usually generates such carcinogenic materials. The biofiltration-ultrafiltration treatment is one of the best solutions to replace treatment plant that using chemicals. It has a low cost operation and is more safe than the water treatment that using chemicals. Generator-set (genset), a power generator that easy to get and operate, has uneconomical operation cost. By now, there were many studies proved that in remote areas, the using of Solar Power Plant is more economic than a genset. For those reasons, in this article is designed a solar powered 50 m3/Day drinking water treatment (biofiltration-ultrafiltration process). The result from the design is the solar power plant that can supply the treatment plant for 8 hours.Ã‚Â Keywords: drinking water, solar power, genset, biofiltration, ultrafiltration.